2011
DOI: 10.1007/s10695-011-9564-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning, characterization expression of P450c17-I and P450c17-II and their functions analysis during the reproductive cycle in males of barfin flounder (Verasper moseri)

Abstract: P450c17, a key steroidogenic enzyme, plays important roles in the production of sex steroid and cortisol. In teleost, there are two types of P450c17, P450c17-I possessing 17α-hydroxylase and 17, 20-lyase activities, and P450c17-II only possessing 17α-hydroxylase activity. This work describes the molecular cloning of the cDNA encoding the barfin flounder (Verasper moseri) P450c17-I and P450c17-II by means of RT-PCR and 5' and 3' rapid amplification of cDNA ends (RACE) analyses and mRNA expression profiles analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Moreover, Pcc-cyp11a1 and Pcc-star transcripts were significantly higher in hepatopancreas, muscle, and spleen tissues. cyp17a1 transcripts were found in gonads of medaka, tilapia, zebrafish, and barfin flounder (Jin et al, 2012), and transcripts were also found in brain and gonadal tissues of half-smooth tongue-sole (Chen et al, 2010) and in both kidney and gonad tissues of Korean rockfish (Mu et al, 2013). cyp17a1 was found to be a key factor associated with mature oocyte cells, and Pcc-cyp17a1 transcripts were only found in ovary, hepatopancreas, eye, and gill tissues in the present study, which demonstrated that steroidogenic genes were involved in gonadal development of gynogenic Pcc-zp, a female-specific gene associated with ovarian development, was present in ovary tissues before being transported to hepatopancreas tissue (Modig et al, 2006), which contains hepatic-specific and ovarian-specific expression patterns (Wu et al, 2012).…”
Section: Tissue-specific Distribution Of the Target Genesmentioning
confidence: 99%
“…Moreover, Pcc-cyp11a1 and Pcc-star transcripts were significantly higher in hepatopancreas, muscle, and spleen tissues. cyp17a1 transcripts were found in gonads of medaka, tilapia, zebrafish, and barfin flounder (Jin et al, 2012), and transcripts were also found in brain and gonadal tissues of half-smooth tongue-sole (Chen et al, 2010) and in both kidney and gonad tissues of Korean rockfish (Mu et al, 2013). cyp17a1 was found to be a key factor associated with mature oocyte cells, and Pcc-cyp17a1 transcripts were only found in ovary, hepatopancreas, eye, and gill tissues in the present study, which demonstrated that steroidogenic genes were involved in gonadal development of gynogenic Pcc-zp, a female-specific gene associated with ovarian development, was present in ovary tissues before being transported to hepatopancreas tissue (Modig et al, 2006), which contains hepatic-specific and ovarian-specific expression patterns (Wu et al, 2012).…”
Section: Tissue-specific Distribution Of the Target Genesmentioning
confidence: 99%
“…In contrast, duplicated cyp17a genes, i.e. cyp17a1 and cyp17a2 , were isolated from the genomes of several teleosts and suspected to synergistically catalyzing the synthesis of C18, C19 and C21 steroid hormones ( 20 22 ). Previous reports revealed that cyp17a1 gene mutation ceased both androgens and estrogens production, and caused spermiation disorder, infertility and all-male population production ( 23 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that P450c17-II is responsible for the production of 17a, 20b-dihydroxy-4-pregnen-3-one during oocyte maturation and cortisol production in the head kidney of Tilapias [48]. In barfin flounder (Verasper moseri),only P450c17-II is involved in the production of cortisol [16].…”
Section: Introductionmentioning
confidence: 99%